The effect of education on knowledge and attitudes in using halal cosmetic products - Siti Lailaturrohmah; Alviyana Lutviyani (Journal of Halal Product and Research)
Consumers' awareness of halal cosmetics is still low. The high level of dependence on a product and the lack of consumer knowledge of cosmetic ingredients makes it difficult for consumers to switch to cosmetic products that are halal certified. Minimal education that is easily accessible regarding the halalness of a cosmetic product among the community is a problem that results in the lack of awareness of halal. This study aims to obtain information about the effect of halal education on knowledge and attitudes in the use of cosmetics. The method used in this study is an experimental design with a sample size of 30 respondents who are active users of cosmetics both labeled halal and not labeled halal. The sampling technique used was accidental sampling. Data on the knowledge and halal attitudes of respondents before and after education were obtained from filling out questionnaires which were carried out online. The data analysis technique used was the Wilcoxon Sign Rank Test using SPSS 16. The results of the respondents' research indicated that there were significant differences in their knowledge and attitudes towards the use of cosmetics before and after halal education with p value â‰¤ 0.05.